Juridical Analysis of the Enactment of a Minimum Limit of 30% Representation of Female Legislative Candidates in Article 8 (2) of KPU Regulation Number 10 of 2023 in the Perspective of the Election Law - Adira Sitanggang; Haposan Siallagan; Januari Sihotang (Journal of Legal and Cultural Analytics, 2025)
This research analyzes the compatibility of Article 8 paragraph (2) of KPU Regulation No. 10 of 2023 with Election Law No. 7 of 2017 regarding women's representation in Indonesian politics. PKPU Article 8 paragraph (2) of KPU Regulation No. 10 of 2023 regulates the calculation method that applies rounding down for numbers below 50, potentially reducing the number of elected female legislative candidates and this research also identifies the challenges and obstacles faced in implementing the 30% quota for women's representation, including the lack of sanctions for political parties that do not meet the quota. This research uses the Library Research method to analyze the compatibility between the provisions in Article 8 paragraph 2 of PKPU No. 10 of 2023 with the principles stipulated in Election Law No. 7 of 2017 related to women's representation as well as the challenges and obstacles faced in the implementation of the quota of women's representation in the legislature after the enactment of PKPU No. 10 of 2023.